Número 10 (La Lupa. Colección fueguina de divulgación científica, 2017)
Comité EditorialMag. Érika Bedoya AgudeloLic. Javier RojoLic. Sebastián CaoLic. Vanesa ParmigianiDra. María Eugenia BarrantesLic. María Eugenia LopezMag. María Laura BorlaDr. Fernando SantiagoLic. Pablo JusimLic. Samanta DodinoDiseño e ImpresiónM&A diseño y comunicación S.R.L.Área Cuatro S.R.L.Buenos Aires, Argentina.E-mail: info@myaweb.com.arContacto: coleccionlalupa @gmail.com